Experience of Surgical Treatment of Complex Forms of Ebstein’s Anomaly through the Method of Hemodynamic Correction - Dziuryi, Ivan V.; Truba, Iaroslav P.; Golovenko, Oleksandr S.; Perepeka, Iryna A.; Lazoryshynets, Vasyl V. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Ebstein’s anomaly (EA) is a rare and complex congenital heart disease, with a prevalence of 4 to 7 cases per 100,000 live births. At this stage of the development of EA surgery, significant progress has been made in our understanding and treatment of EA, but the question of the tactics of treating complex forms, especially in the period of infancy and early childhood, remains open. Due to significant phenotypic heterogeneity, the treatment of EA varies greatly from patient to patient and depends on many factors that require a comprehensive approach. The choice of the method of surgical correction directly depends on the anatomical features: the degree of dysplasia, rotation and displacement of the tricuspid valve, the degree of atrialization of the right ventricle, the combination with other congenital heart diseases, and the severity of hemodynamic disorders. The aim. To evaluate perioperative characteristics in patients with complex forms of EA, immediate and long-term results after hemodynamic correction. Materials and methods. In the period from 1996 to 2022, at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine, one and a half ventricle repair was performed in 18 patients with complex forms of EA. There were 12 (67%) male patients, 6 (33%) female patients. The median age of the patients at the time of surgery was 30 months [3.5; 312]. The main diagnostic method in determining the defect and assessing the immediate and remote results was echocardiography and probing of the heart cavities. In order to qualitatively evaluate the perioperative, immediate and long-term results to determine the optimal tactics and terms of surgical intervention, prevention of possible complications, all the patients were divided into two age groups: I group up to 2.5 years including 9 patients (50%), II group older than 2.5 years including 9 patients (50%). Results. In the postoperative period, 2 (11%) deaths were noted in both groups. In all the deceased patients, the cause of death was acute heart failure and acute respiratory failure. The analysis of the postoperative period showed normal results in such a cohort of highly complex patients of both groups, but a more stable course was noted among patients of the I group, as indicated by statistically significant values for the duration of mechanical ventilation, stay in the intensive care unit, stay in the hospital, the average dose of sympathomimetic support and its duration, the total duration of exudation in the comparison groups. An uncomplicated course of the early postoperative period was observed in 8 (44%) patients. The remaining 10 (56%) patients of both groups had: I group, 3 (33%) patients: 7 complications; II group, 5 (55%) patients: 13 complications. In 5 patients (2 patients in I group and 3 patients in II group), attention-grabbing acute heart failure was observed, which required high doses and long-term sympathomimetic support, and in 2 patients caused death. The average observation period was 45 months [6; 190]. No deaths were observed during the observation period among 13 (72%) patients of both groups, contact was lost with 3 (17%) patients. There were no violations in the functioning of the right ventricle, but the recovery of the systolic function of the left ventricle occurred only in 8 (44%) patients. Tricuspid insufficiency was minimal in 5 (28%) patients, moderate in 6 (33%), severe in 2 (11%) patients. Conclusions. Determining the tactics of treatment of complex forms of EA is a serious problem in patients of various ages, especially in newborns and infants, due to pronounced dilatation and systolic dysfunction of the left ventricle, a sharp decrease in systemic output due to changes in the geometry of the left ventricle. The technique of hemiventricular correction shows very promising results and may become the technique of choice for patients with severe forms of EA and pronounced right ventricular insufficiency.